(untitled) (Journal of Comparative Social Work, 2011)
This article examines the effects on the professional system of creating a new system for the quality assurance of residential care in the Norwegian child welfare service. Since 2004, all institutions, private as well as governmental, have undergone a quality evaluation process. A set of indicators was given by the Ministry, with the regional authorities expected to assess the institutions according to these indicators.The main purpose of the article is to discuss to what extent, and in which way, the new control system may exert an impact on the jurisdiction of social work and professional practice in the everyday life of the institutions. The discussion is based on empirical data from a project entitled, “A control regime in transition”, which is supported by the previous Ministry for Children and Family Affairs. The project work started at the end of 2004, and followed the new control regime for three and a half years.